Plant impacts on nitrogen and carbon cycling in the Monte Phytogeographical Province, Argentina - Carrera, Analía Lorena (2009)
In arid and semiarid ecosystems, primary productivity and nutrient cycling are directly related to the amount and seasonal distribution of precipitation. However, depending on morphological, phenological, physiological, and biochemical traits, plants may influence the quality and quantity of organic matter inputs to the soil and thus the biomass and activity of the soil biota responsible for carbon and nitrogen dynamics. In this paper, we review the available knowledge on plant functional traits and their impacts on ecosystem processes such as N and C cycling throughout the Monte Phytogeographical Province. We address the mechanisms of N conservation, the quantity and quality of leaf litterfall and root traits of the dominant plant life forms and their effects on decomposition processes, soil organic matter accretion, and soil-N immobilization and mineralization. We conclude that plant functional traits affect ecosystem processes in the Monte Phytogeographical Province since the chemistry of senesced leaves and root biomass exerts an important control on organic matter decomposition and N availability in soil.